OPTIMIZATION OF IPS LEARNING IN CHARACTER FORMATION OF GRADE V STUDENTS AT MIS HIDAYATUSSALAM - Ablia, Zikri; Safran, Safran (Universitas Indraprasta PGRI, 2025)
The purpose of this study was to maximize the use of Social Studies (IPS) education in order to improve the character development of fifth grade students at the Hidayatussalam Private Elementary School. Using a qualitative approach, this study was conducted through observation, document analysis, and in-depth interviews to understand the teacher's perspective and the teaching methods used. The main focus of this study is how IPS education can be integrated with values such as tolerance, honesty, responsibility, cooperation, and respect for others. This study was conducted at the Hidayatussalam Private Elementary School, an Islamic educational institution with a focus on character education. The results of the study indicate that teachers play a central role as role models and facilitators in the formation of student character. Project-based learning methods and group discussions have proven effective in instilling character values. In addition, the selection of relevant teaching materials, the insertion of inspirational stories, and in-depth reflection during the learning process help students understand and internalize positive values. This study shows that optimizing IPS learning through integrative strategies can support the formation of student character holistically. This finding provides an important contribution to the development of learning methods that are not only oriented towards academics, but also towards strengthening students' character.